Your leadership style: why understanding yourself matters. Issue 4 (16th November 2020) - Price-Dowd, Clare Felicity Jane
Abstract : Understanding of personal leadership style has been shown to be a key part of effective leadership practice. It has been a topic of interest for many decades as we have tried to understand, and replicate, what makes those considered to be 'great leaders' so successful. This article gives a brief introduction to different leadership 'theories', leadership 'styles' and the effect they have on the 'climate' in organisations. Having an understanding of the different approaches can help leaders be more effective through comprehending how and why they do what they do, as well as helping them identify where and when they need to adapt their style. By considering how our understanding of leadership has evolved, it is possible to show how effective leadership is not linked to one approach. It is a combination of knowledge, attitudes and behaviours with a focus on both the task in hand and concern for those undertaking that task. Furthermore this understanding supports impactful personal development, which creates positive climates in organisations where compassionate and inclusive leadership behaviours can, and do result in better outcomes for staff and patients.